Atendimento Educacional Especializado em escolas de tempo integral da Rede Municipal de Ensino de São Paulo - Gomes-Silva, Amanda Santana (Universidade Federal de São Carlos, 2022)
The demand for Specialized Educational Assistance (SEA) has been growing considerably in Brazil, as well as Integral Education, possibly because of Public Policies such as Fundeb and the National Education Plan (NEP). The NEP establishes the offer of Education full-time, with a minimum stay of seven hours a day at school, in at least half of the schools by the year 2024. However, educational policies are not always convergent, when they recommend, for example, that SEA for students with Special Educational Needs (SEN) is an extra-class offer, in contrast to school shifts, and at the same time foresee an increase in the offer of full-time schools. In these cases, it is worth questioning how schools with full-time education are equating the SEA, which cannot be offered in the counter shift? The city of São Paulo instituted in its policy three modalities of SEA: Collaborative, Itinerant and Counter-shift. Thus, based on the theoretical-methodological framework of the Policy Cycle Approach to analyze educational policies, the present study aimed to describe and analyze how SEA is equated in full-time schools of one of the regional division of education in that municipality. The investigation involved three schools, with the participation of 22 regular teachers, two specialized teachers and six principals. Data collection involved document analysis, questionnaires with open and closed questions and systematic observation. The teachers of regular education pointed out the importance of working collaboratively, in partnership with a specialized teacher. In schools where there was no specialized teacher, teachers pointed out the need for this professional to serve SEN students. Teachers highlighted the importance of school projects considering the integrality of subjects and school inclusion as a way of promoting the participation of all indiscriminately. The study suggests that full-time Integral Education tends to expand the possibilities of SEA, in addition to exclusively extracurricular AEE, in shifts, and in resource rooms, a model prioritized in Brazilian Special Education policies.
Specialized Educational Assistance in full-time School Integral of the Municipal Education network of São Paulo
Asistencia Educativa Especializada en escuelas de tiempo completo de la Red Municipal de Educación de São Paulo
Keywords: Política pública educacional; Abordagem do ciclo de políticas; Educação Especial; AEE colaborativo; Educação integral; Public educational policy; Approach to the policy cycle; Special Education; Full-time school; Co-teaching specialized educational assistance; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO